PENERAPAN GOOD GOVERNANCE DALAM MEMBANGUN APARATUR PEMERINTAHAN YANG BERSIH DAN BEBAS DARI KKN - Mahmuda Pancawisma Febriharini (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
Conditions of government officers at this show is not a good image and performance of government administration so that the performance of duties of public administration and development both at central and regional levels have not been implemented based on the principles of good governance (good governance). Faced with this situation needed improvement of public services, transparency and accountability of government performance to the public, as well as the presence of an oversight or control over the government's performance both by formal oversight institutions and the supervision carried out by the public as part of community participation towards the implementation of development.